New Light on Chromotherapy: Grakov's 'Virtual Scanning' System of Medical Assessment and Treatment. Issue 2 (2007) - Hankey, Alex; Ewing, Elena
Abstract : Virtual Scanning incorporates novel uses of colored light into its system of health assessment and therapy. Independent investigations of its effectiveness in Russia and the UK have revealed unique abilities to correct incipient and fully developed chronic conditions. As such it forms an important new addition to the field of Chromotherapy. It differs from most others, in that its development depended on discoveries in neuroscience by its inventor, and subsequent application of new models in computational neuroscience.